CLASSROOM INTERVENTION: READING TONI MORRISONâ€™S A MERCY WITHIN INDONESIAN CONTEXT - Manggong, Lestari (Jurnal Pendidikan Bahasa dan Sastra, 2017)
Since knowledge often suits a situation, knowledge can work as a strategy. Spivak (1993) emphasizes that classroom can be staged as intervention. In the classroom, a case, a theory, or a concept is proposed, and students are encouraged to intervene. In Spivakâ€™s â€œteaching machineâ€, it is strategic to always move outside and not be like the mainstream. To do this, one must inhabit, invest, and criticize the knowledge put in hand. With this in mind, this essay attempts to explore how reading literature can help Indonesians negotiate their identities across languages, generations, and cultures, and in the end, would look critically at the politics of identity and culture. This article argues that reading Toni Morrisonâ€™s A Mercy provides perspectives on the relevance of teaching American literature within Indonesian context. Tzvetan Todorovâ€™s (1982) theory on the conquest of other helps the analysis on the novelâ€™s colonial issue, while the conquest of America by female characters in the novel is discussed within the frame of feminist studies. Intervention in this case is conducted to question what can be reflected upon such issues for students in Indonesia whose country experienced (post)colonialism and is continuously tackling with the issue of gender equality.Keywords: American literature; feminist studies; Indonesian context; intervention; (post)colonialismKarena pengetahuan sering sesuai dengan situasi, pengetahuan dapat digunakan sebagai strategi. Spivak (1993) menekankan bahwa ruang kelas dapat dikondisikan sebagai medium intervensi. Di ruang kelas, sebuah kasus, teori, atau konsep diajukan, dan siswa didorong untuk melakukan intervensi. Dalam konteks mesin pengajaran yang dikonsepkan oleh Spivak, selalu bergerak keluar (tidak mainstream) merupakan hal yang sangat strategis untuk dilakukan. Untuk dapat melakukan ini, seseorang harus benar-benar memahami, menginvestasikan, dan mengkritik pengetahuan yang ada. Atas dasar pemikiran ini, artikel ini mencoba untuk mengeksplorasi bagaimana membaca karya sastra dapat membantu orang Indonesia menegosiasikan identitas mereka melalui bahasa, generasi, dan budaya. Hingga pada akhirnya, akan terlihat kritik terhadap politik identitas dan budaya. Artikel ini berargumentasi bahwa membaca novel A Mercy karya Toni Morrison dapat memberikan perspektif tentang relevansi pengajaran sastra Amerika dalam konteks Indonesia. Teori Tzvetan Todorov (1982) tentang penaklukan yang lain membantu analisis isu kolonial novel tersebut, sementara penaklukan Amerika oleh tokoh perempuan dalam novel tersebut akan dibahas dalam kerangka studi feminis. Intervensi dalam kasus ini dilakukan untuk mempertanyakan apa yang dapat tercermin pada isu-isu tersebut bagi siswa di Indonesia yang negaranya mengalami kolonialisme dan terus-menerus menangani masalah kesetaraan jender.Kata kunci: kesusastraan Amerika; kajian feminis; konteks Indonesia;intervensi; (pos)kolonialismeÂ Â